2019
DOI: 10.1029/2017tc004832
|View full text |Cite
|
Sign up to set email alerts
|

Oligocene‐Early Miocene Topographic Relief Generation of Southeastern Tibet Triggered by Thrusting

Abstract: The timing and mechanisms of uplift in southeastern Tibet remain disputed. To address this debate, we conducted structural and morphological analyses of the Yulong thrust belt; we also reconstruct the cooling and exhumation history of the Jianchuan basin in the hanging wall of the thrust system using inverse thermal modeling of apatite fission-track and (U-Th)/He thermochronology data. Our results provide evidence for 2.3-3.2 km of rapid exhumation in the Jianchuan basin between~28 and~20 Ma, followed by limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 71 publications
(162 reference statements)
5
85
0
Order By: Relevance
“…However, in the same area, Yang et al (2016) reported a late Eocene AHe age. Based on AHe ages ranging from 30 to 20 Ma, Shen et al (2016) proposed that incision occurred during the Miocene-early Oligocene, which was confirmed by new AHe and fission-track data by Cao et al (2019), who showed a rapid exhumation phase from 28 to 20 Ma. Downstream of the Yangtze first bend, in the Tiger Leap Gorge (TLG in Fig.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…However, in the same area, Yang et al (2016) reported a late Eocene AHe age. Based on AHe ages ranging from 30 to 20 Ma, Shen et al (2016) proposed that incision occurred during the Miocene-early Oligocene, which was confirmed by new AHe and fission-track data by Cao et al (2019), who showed a rapid exhumation phase from 28 to 20 Ma. Downstream of the Yangtze first bend, in the Tiger Leap Gorge (TLG in Fig.…”
Section: Introductionmentioning
confidence: 77%
“…3) a few kilometers north. Last, Cao et al (2019) collected two samples in the same area that yielded mean AHe ages of ca. 38 and 30 Ma.…”
Section: Local Incision History and Its Implications For The Cenozoicmentioning
confidence: 99%
See 2 more Smart Citations
“…This timescale correlated with the conclusion of the initial uplift of the QTP during the early Miocene (25 ~ 17 mya; Shi et al, ). The extensive uplift of the Himalayas and subsequent uplift of the Southeastern Tibet and Yunnan Plateau (Figure S2) during the early Miocene to Pliocene (Cao et al, ; Favre et al, ; Harrison, Copeland, Kidd, & Yin, ; Ruddiman, ; Shi et al, ) would have completely divided the Bellamya lineage in the Pearl River basin from that in India and Thailand. Many studies have associated the divergence of organisms, such as in lizards, birds, frogs and fish, with the Miocene uplift of the QTP and simultaneous climate changes (Che et al, ; Guo & Wang, ; Johansson et al, ; Wang, Gan, Li, Chen, & He, ).…”
Section: Discussionmentioning
confidence: 99%